Raspberry Pi based cyber physical system for vehicle monitoring over internet - Lee, Kar Chun (2023)
This paper is about an embedded system design and a development project for academic purpose. The project will offer the methodology, concept, design and development flow of an embedded system to students who are interested in it. This will be practiced by the building of an embedded system using a mini computer. Since Raspberry’s technology is well suited for beginners and students to learn and practice building a simple system, it is therefore implemented in the project by the use of Raspberry Pi 3B+. From a design perspective, the emphasis is on the embedded system design process. The design flows start by problem abstraction, hardware – software architecture, system related family of design referencing, modular design, software mapping, user interface design and refinement. It is crucial to abstract the problem and uses the appropriate hardware and software to create a system that truly solves the problem. Emphasis is also made on the importance of designing the PCB’s board for hardware components to be shouldered on and connects to the computer. Therefore, an EDA tool such as EAGLE which is used in this project is important in incorporating into the design flow and aids the system to have a low noise and interference, ease of testing and repair plus compact design. With the help of an EDA tool, the project outcome will be sleeker and easier to have a checkup on sensors and connections and also for aesthetic purposes. Moving on, the system will have to connect to a platform, mobile application in this case, to transfer and store data collected from the sensors. The platform will be able to display the data for users to refer. With each type of data collected such as temperature, humidity and gas quality, it is displayed in the app with texts and numbers. For latitude and longitude, the platform will be displaying them with a map and pin widget for users to refer. It is done so to ease the users to understand the condition inside the vehicle and also the whereabouts of the vehicle. With the display features designed and completed, the alarm features have to be implemented to alarm users when there is a dangerous event occurred inside the vehicle. The system is built to have a buzzer and will buzz when there are unwanted events happened like high temperature, high humidity and dangerous gases detected when users is in the vehicle. When the users’ parked vehicle is moved, the platform should also send a message through notification on users’ phone to alert them that their vehicle is moved and there is a possible vehicle theft happening.